2021
DOI: 10.1007/s10570-021-04253-3
|View full text |Cite
|
Sign up to set email alerts
|

Water-accessibility of interfibrillar spaces in spruce wood cell walls

Abstract: Water interactions and accessibility of the nanoscale components of plant cell walls influence their properties and processability in relation to many applications. We investigated the water-accessibility of nanoscale pores within the fibrillar structures of unmodified Norway spruce cell walls by small-angle neutron scattering (SANS) and Fourier-transform infra-red (FTIR) spectroscopy. The different sensitivity of SANS to hydrogenated ($$\hbox {H}_2\hbox {O}$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The d c value obtained for the D‐wood veneer corresponded well with previous results obtained from delignified birch (3 nm) [ 25 ] and native spruce wood (3.9 nm). [ 26 ] Thus, there was no significant change in the wood microstructure in terms of the organization of cellulose microfibrils in the D‐wood veneer as compared to native wood. Interestingly, the increased d c value obtained after LPMO oxidation revealed a profound change in the organization of cellulose microfibrils in the wood cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…The d c value obtained for the D‐wood veneer corresponded well with previous results obtained from delignified birch (3 nm) [ 25 ] and native spruce wood (3.9 nm). [ 26 ] Thus, there was no significant change in the wood microstructure in terms of the organization of cellulose microfibrils in the D‐wood veneer as compared to native wood. Interestingly, the increased d c value obtained after LPMO oxidation revealed a profound change in the organization of cellulose microfibrils in the wood cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…Small angle scattering is one of the structural analyses methods gaining popularity in the field of wood science. For example, Penttilä et al have studied the relationship between moisture content changes and microstructures changes in wood using X-ray and neutron scattering [13,14,26]. In these experiments, in situ measurement plays an important role, which is one of the advantages of small-angle scattering.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Results of SAXS fits using the WoodSAS model (SI eq S3) (see Figure S13 for all results). (b) Microfibril packing distance as a function of MC (0.7 × MC c ) as determined from the periodic bundle model (see Figure S15 for non-periodic model) and a comparison to experimental SAXS and SANS results ,,,,, (MC of 41% used for Norway spruce in water-saturated state; error bars correspond to standard deviation between samples). Snapshots of the periodic model with density of water in blue are shown on the right.…”
mentioning
confidence: 99%
“…Other works have reported abrupt changes in the mechanical properties of wood, its susceptibility to fungal degradation, and water diffusion and hydrogen bonding at 22 (see Figure S13 for all results). (b) Microfibril packing distance as a function of MC (0.7 × MC c ) as determined from the periodic bundle model (see Figure S15 for non-periodic model) and a comparison to experimental SAXS and SANS results 20,22,23,29,58,59 (MC of 41% used for Norway spruce in water-saturated state; 39 similar MCs, 60−62 which coincides with the softening of hemicelluloses. 3 A previous diffraction study also found the largest moisture-related changes in the lattice parameters of spruce wood cellulose below MC 13%.…”
mentioning
confidence: 99%